Central and peripheral contributions to the effect of glucose ingestion on maximal force production - Pang, Benedict Wei Jun (2018)
Purpose: To investigate the effects of carbohydrate ingestion on maximal force production, and distinguish the relative central and peripheral contributions. Methods: In a randomised double-blind crossover design, eight healthy and physically active males ingested 100 mL of either 10% (w/v) glucose, 0.05% (w/v) aspartame, 9% (w/v) maltodextrin, or water. Changes in torque production, electromyographic data, neuromuscular function, blood parameters and perceptual variables during maximal voluntary contractions were assessed through voluntary and electrically evoked contractions before and after ingesting the solutions. Results: Blood glucose concentrations were significantly elevated from baseline values in the glucose and maltodextrin trials (p < 0.01) while blood lactate concentrations were similar across time and between trials (p > 0.05). Perceptual ratings were unchanged across time (p > 0.05), except for RPE in response to exercise (p < 0.01), and scores were similar between trials (p > 0.05). All parameters of the neuromuscular function, voluntary activation, potentiated twitch torques, low-frequency fatigue ratio and EMG activity did not differ between trials or across time (p > 0.05). Conclusions: Glucose ingestion alone does not improve maximal force production or neuromuscular function during maximal voluntary contractions. A combined glucose ingestion and glucose mouth rinsing protocol may be required to mediate a significant improvement in maximal force production.